The EU and supplementary pensions. Instruments for integration and the market for occupational pensions in Europe - Guardiancich, Igor; Natali, David (Brussels, 2009)
"Reliance on private retirement pensions is on the increase both at Member State level, via the spread of quasi-mandatory occupational plans, and at EU level, as a result of initiatives including the IORP Directive. This Working Paper analyses the legislative and market trends that underpin this development, assessing the impact of the global financial crisis, presenting the regulatory improvements required, and delineating the future prospects of the market for supplementary pensions. "